(untitled) (Journal of Economic Research & Business Administration, 2024)
Today, due to the fact that the Republic of Kazakhstan is going through a difficult period due to a global pandemic, a decline in business activity due to the geopolitical situation and national security challenges, the creation of work-friendly jobs in order to improve the welfare of the population, reduce the income gap and ensure income is one of the most important tasks of the state. The relevance of the research topic is due to the need to strengthen the effectiveness of the policy of state regulation of income of the population, the purpose of which is to increase the income of the population on the basis of employment, protection from fluctuations in the economic situation and assistance to socially vulnerable segments of the population. Changes in the sphere of formation and distribution of incomes of the population in modern conditions of state development, the constant change in the system of inter-budgetary relations determine the relevance of the study of the problem of state regulation of incomes of the population. The purpose of the article is to determine the role of state regulation of income of the population in the socio–economic development of the country in the Republic of Kazakhstan. The article reviews the system of state regulation of incomes of the population in the Republic of Kazakhstan and its main methods, evaluates the main socio-economic indicators and provides recommendations for improving the system of state regulation of incomes of the population in the Republic of Kazakhstan. In general, the inability to ensure stable income growth of the population, a relatively low level of labor income, high self-employment of the population, failure to achieve goals for real income growth in the future are risks that have a significant impact on the socio-economic development of the country. As a result of the conducted research, the authors come to the conclusion that in order to ensure the socio-economic development of the country, it is necessary to improve the system of state regulation of incomes of the population. Methods of systematic, analytical, economic and statistical analysis were used in the study. The statistical data of the World Bank, the National Bureau of Statistics of the Agency of the Republic of Kazakhstan for Strategic Planning and Reforms were used as the materials of the scientific research. The value of the conducted research is characterized by the possibility of applying the results of the study by state regulatory bodies in the development of state policy in the field of state regulation of income of the population in the Republic of Kazakhstan. Key words: income of the population, state regulation, poverty, social inequality, living wage.